2019
DOI: 10.3389/fnagi.2019.00280
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Application of Virtual Reality Technology in the Diagnosis and Treatment of Cognitive Impairment

Abstract: At present, with the development of an aging society and an increase in the number of elderly people, in order to ensure the ability and enthusiasm of the elderly to live independently, it is necessary to ensure that they can understand the world in a normal way. More and more elderly people have cognitive impairment, and virtual reality (VR) technology is more effective in cognitive diagnosis and treatment than traditional methods. This review article describes some studies on cognitive diagnosis and training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(33 citation statements)
references
References 20 publications
(22 reference statements)
0
33
0
Order By: Relevance
“…In this regard, Cotelli and Colleagues argue that currently the available evidence is insufficient to draw conclusions about the effects of tele-rehabilitation on cognition, health related quality of life or participant satisfaction, highlighting that the quality of the clinical studies' designs need to be improved. An encouragement to the tele-rehabilitation use comes from a recent review that confirms Virtual-reality technology as a very effective tool for cognitive assessment and recovery in patients with cognitive impairment (51). Moreover, a recent meta-analysis conducted on Exergames (Physically-active video games) concluded that benefits were observed with this kind of treatment for both healthy elderly and clinical populations with cognitive impairments (52).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Cotelli and Colleagues argue that currently the available evidence is insufficient to draw conclusions about the effects of tele-rehabilitation on cognition, health related quality of life or participant satisfaction, highlighting that the quality of the clinical studies' designs need to be improved. An encouragement to the tele-rehabilitation use comes from a recent review that confirms Virtual-reality technology as a very effective tool for cognitive assessment and recovery in patients with cognitive impairment (51). Moreover, a recent meta-analysis conducted on Exergames (Physically-active video games) concluded that benefits were observed with this kind of treatment for both healthy elderly and clinical populations with cognitive impairments (52).…”
Section: Discussionmentioning
confidence: 99%
“…In summary, VR provides participants a feeling of presence that is similar to real life [ 23 , 24 ]. The present study demonstrated that VR technology, such as the VRCTS, was a time-saving, efficient and attractive method to evaluate cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…The combined system enables us to measure eye movements while showing VR animations. VR is also an effective tool for both diagnosis and intervention in the research field of neurodegenerative disorders ( 16 18 ). Previous studies reported that interventions with using VR technology improved motor and cognitive functions of people with disorders such as stroke, MCI, AD, and PD ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%